(3GdLGeY GdcHjQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3jHJOF HMOjK dGjUdjf GMO Yf GMO hdGjUO ef GMO Yf GMO s
(3BNQgG (B:s
(3jfJgi HMOjK Yf CHj gQjQI Gfge JPcQhG GdUdGI GdhSWi hbG GNJdafG ajgG s
(3HgG fXGe GdJYbjHIs
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdMOjK h GdeUWdMs